2021
DOI: 10.32736/sisfokom.v10i1.1068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Trust on the Use of FinTech (P2P Lending) in Indonesia

Abstract: Since 2016 the P2P Lending industry has begun to develop in Indonesia. Peer to Peer Lending (P2P Lending) is a new alternative to getting funds in the form of money loans to individuals or investors. Fintech P2P Lending provides convenience through a simple and fast service. Its features can be accessed by anyone, anytime, anywhere. On the other hand, investors or lenders have investment alternatives with attractive returns. So that it quickly spread to all segments of Indonesian society. The purpose of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
(9 reference statements)
2
5
1
1
Order By: Relevance
“…Penelitian sebelumnya menemukan bahwa jaminan keamanan memiliki pengaruh yang signifikan terhadap minat investasi fintech lending, seperti yang dinyatakan pada [21]. Berdasarkan penelitian tersebut, peneliti ingin menganalisis apakah jaminan keamanan memiliki pengaruh positif terhadap fintech lending minat investasi di Indonesia.…”
Section: Pengaruh Jaminan Keamanan Terhadap Minat Investasiunclassified
“…Penelitian sebelumnya menemukan bahwa jaminan keamanan memiliki pengaruh yang signifikan terhadap minat investasi fintech lending, seperti yang dinyatakan pada [21]. Berdasarkan penelitian tersebut, peneliti ingin menganalisis apakah jaminan keamanan memiliki pengaruh positif terhadap fintech lending minat investasi di Indonesia.…”
Section: Pengaruh Jaminan Keamanan Terhadap Minat Investasiunclassified
“…Brand Image is the perception and feeling consumers have about a brand, which drives customer behaviour (Zhang, 2015) based on personal experience or information obtained from others (Pratama, 2021). To build brand image, company set up marketing strategies to change how people think about and feel about a brand, create an image of the brand in people's minds, and get people to buy the brand.…”
Section: Brand Imagementioning
confidence: 99%
“…The findings of this study were consistent with some number of earlier studies. First, research conducted by (Pratama, 2021) indicates that the public's perception of a company's brand increases a positive and significant impact on their confidence when using financial technology. Digital Banks with a higher reputation will gain more client trust.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…The indicators of trust according to Vance et al ( 2008) are confidentiality, integrity, availability, authentication, accountability, assurance, privacy, and authorization which essentially can affect the beliefs and intentions of trust. In previous research, integrity was not significant to trust in using FinTech (Pratama, 2021). Therefore, the following hypothesis is proposed: H2: integrity has a positive effect on trust in use Perception of ease of use refers to the extent to which the use of a system does not require additional effort at the user's skill and knowledge level (Ismagilova, et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Brand image is a representation of the entire product or consumer assessment of a product brand. This formation can be made based on personal experience or hearing about its reputation from others or the media (Pratama, 2021). Yu-shan (2010) was found that brand image has a positive and significant effect on trust in use.…”
Section: Introductionmentioning
confidence: 99%